Sectorial Climate Change Impacts and Adaptation in Benin - Badou, Djigbo Félicien; Yegbemey, Rosaine N.; Hounkpè, Jean (Handbook of Climate Change Management, 2021)
This chapter gives a broad yet concise overview of climate change impacts and adaptation in selected sectors in Benin. First, the chapter documents climate change impacts, highlighting more or less studied sectors/areas, current adaptation efforts and required improvements. Second, the chapter presents the institutional framework of climate change policies, the roles of civil society and the provision and utilization of climate information services in combating climate change. A search and screening of scholarly articles, technical reports and newspapers were conducted to identify and select relevant literature for the review. Findings suggest that climate change in Benin is characterized by increases in temperature, sea-level rise and extreme events such as floods, droughts and strong winds. The main sectors/areas where impacts are documented include water resources, agriculture, energy, health, and costal ecosystems. Water resources and agriculture are the most studied sectors while health and energy have received a limited attention so far. At both the institutional and civil society levels adaptation strategies are designed, implemented and planned either based on indigenous initiatives or through bilateral and multilateral cooperation. These strategies have strengths and weaknesses. Awareness on the usefulness, availability, and accessibility to climate information services is still limited. This review provides recommendations to support the current national effort in building a more resilient and climate smart society
Keywords: Climate change adaptation; water resources; agriculture; health; costal ecosystems; Benin; C2EA; University of Abomey Calavi; Benin